Analysis of the Effect of Damdex Addition to Concrete Mixture on Compressive Strength - Endah Murtiana Sari; Probokusumo; Alfiya Rokhmah; Muhamad Dzaky Ashidqi; Rahmat; Thomas Junaedi (Engineering Science Letter, 2025)
This study aims to determine the compressive strength and modulus of elasticity of concrete with the addition of Damdex variables to obtain the best composition. This research method is classified as quantitative research conducted at PT. Fresh Beton Indonesia Batching Plan BSD. In this study, research was conducted using two different concrete mixtures, namely 1 Pc: 2 S: 3 Gr and 1 Pc: 3 S: 2 Gr, each of which was supplemented with Damdex at concentrations of 0.0%, 0.2%, 0.4%, and 0.6%. According to the study's results, the highest compressive strength and modulus of elasticity were achieved in a concrete mixture of 1 Pc: 2 S: 3 Gr, with a variable addition of Damdex at 0.2%, resulting in a compressive strength of Fc 15.11 MPa and a modulus of elasticity of 18975.061 MPa. Meanwhile, the lowest compressive strength and modulus of elasticity results were obtained in the concrete mixture of 1 Pc: 2 S: 3 Gr with the variable addition of Damdex 0.6%, with a compressive strength of Fc 12.90 MPa and a modulus of elasticity of 17049.89 MPa. In the concrete mixture of 1 Pc: 3 S: 2 Gr, the compressive strength and modulus of elasticity were smaller compared to the concrete mixture of 1 Pc: 2 S: 3 Gr, with the highest results in the variable addition of Damdex 0.2%, with a compressive strength of Fc 9.89 MPa and a modulus of elasticity of 13846.477 MPa. Compressive strength and elastic modulus were measured at 28 days in accordance with SNI 1974:1990/2847 procedures. Among the tested mixtures, the 0.20% Damdex addition achieved the highest average compressive strength and elastic modulus. Within the tested conditions, 0.20% Damdex provided the best average performance; however, further work with larger samples and additional durability metrics is needed to confirm this trend.